INTELLECTUAL CAPITAL AND CAPITAL STRUCTURE ON COMPANY VALUE IN THE INDUSTRIAL SECTOR REGISTERED ON THE BEI FOR THE 2018-2022 PERIOD - Lidya Martha; Sri Rahayu (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
This research aims to examine the influence of intellectual capital and capital structure on company value in the industrial sector listed on the idx 2018-2022. This type of research is quantitative. The population in this study wa 61 industrial companies. The sample in this study was 20 companies. The data source in this research is secondary data. The data collection technique uses documentation thecniqueswith the helpof the eviewa 8 program. The hypotesis is tested using the t test at α =0.05. The reseults of this research show that intellectual capital has a positive effect on company value and capital structure has a negative effect on company value in the industrial sector lidted on the BEI 2018-2022 period.